Analysis of Turkish Science Education Curricula's Learning Outcomes According to Science Process Skills - Ozkan, Gulbin; Umdu Topsakal, Unsal (Universitas Pendidikan Indonesia, 2021)
This study aims at analyzing the learning outcomes of the 2018 science education curricula in Turkey according to science process skills. Learning outcomes are statements that describe what a learner will know, understand, and/or be able to do after completing a learning process. Learning outcomes were evaluated using document analysis which is a qualitative research method. There were 269 learning outcomes analyzed from the curricula . The science learning outcomes in the curricula which are prepared by the Turkey Ministry of National Education, were examined, starting from fourth-grade to eighth-grade levels. The results show that the least common science process skills are â€œmeasuringâ€ and â€œhypothesizingâ€ dimensions, while the most common are â€œdata interpretingâ€ and â€œinferringâ€ dimensions. The highest science learning outcomes are at the seventh-grade level, and the least science learning outcomes are at the fifth-grade level. As the grade level increases, it is seen that more learning outcomes represent higher-level skills. The number of basic science process skills of the fourth-grade level learning outcomes is higher than the number of integrated science process skills, and the number of integrated science process skills is high in learning outcomes at all other grade levels.